Development of Four-tier Diagnostic Test Instrument to Introduce Misconceptions and Identify Causes of Student Misconceptions in the Sub-topic of Bernoulli's Principle - Jumilah Jumilah; Wasis Wasis (Postgraduate, University of Mataram, 2023)
The objective of this study is to create a misconception test instrument for identifying and understanding misconceptions in students regarding Bernoulli's Principle, particularly during hybrid learning. The validity and reliability of the test instrument are described in order to assess its effectiveness. Descriptive analysis techniques were employed to analyze the data. The findings revealed that the test instrument exhibits high validity (94.16%) and reliability (0.72%). On average, 34.9% of students were found to possess misconceptions regarding the sub-topic of Bernoulli's Principle. Item number 5 was identified as having the highest misconception rate (53%), specifically in relation to determining the speed of airflow above and below an aircraft's wings. These findings indicate that some students lack a comprehensive understanding of the fundamental concepts underlying Bernoulli's Principle, relying solely on its equations. Consequently, this research suggests that teachers can mitigate misconceptions and identify their causes by employing a four-tier diagnostic test, especially in the context of the sub-topic of Bernoulli's Principle